Controversies in the treatment of idiopathic membranous nephropathy - Waldman, Meryl (2009)
Optimum treatment of idiopathic membranous nephropathy is both controversial and challenging. The most extensively studied and frequently used immunosuppressive regimens for this disease comprise alkylating agents plus corticosteroids or ciclosporin. All of these treatment options have inherent problems: they are not effective in all patients, partial—rather than complete—remissions are common, adverse effects are worrisome, and relapses after treatment cessation remain problematic. Alternative immunosuppressive agents have been tested in an effort to overcome these unresolved issues. This paper reviews the available evidence regarding both established and new agents for the treatment of patients with idiopathic membranous nephropathy, with an emphasis on the results of the most recent clinical trials.